2022
DOI: 10.3390/d14050395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aquatic Vegetation Restoration after Removal of Culture Purse Seine on Phytoplankton Community Structure in Caizi Lakes

Abstract: Many reports have demonstrated that the removal of aquaculture purse seine is conducive to the restoration of aquatic vegetation and the improvement in water quality, but less attention has been paid to the effects on phytoplankton. This paper addressed the response of phytoplankton community structure to aquatic vegetation restoration after purse seine removal in Caizi Lakes. The results showed that the average dissolved oxygen (from 7.43 ± 0.25 mg/L to 9.12 ± 0.49 mg/L) and Secchi depth (from 28.40 ± 6.20 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The gut microbiota and ARGs in A. erythropus wintering at the two lakes were correlated with the physicochemical properties of the two lakes. It was previously reported that the concentrations of chemical ions in the surface and groundwater of the study area were higher than those of atmospheric precipitation, while total phosphorus, total nitrogen, chlorophyll-a, and transparency values of the surface water pointed to eutrophication (Cui et al, 2021 ; Gao et al, 2022 ; Zhao et al, 2022 ). The trophic state index and bacterial eutrophic index values showed that the two lakes were slightly eutrophic (Gao et al, 2022 ; Zhao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The gut microbiota and ARGs in A. erythropus wintering at the two lakes were correlated with the physicochemical properties of the two lakes. It was previously reported that the concentrations of chemical ions in the surface and groundwater of the study area were higher than those of atmospheric precipitation, while total phosphorus, total nitrogen, chlorophyll-a, and transparency values of the surface water pointed to eutrophication (Cui et al, 2021 ; Gao et al, 2022 ; Zhao et al, 2022 ). The trophic state index and bacterial eutrophic index values showed that the two lakes were slightly eutrophic (Gao et al, 2022 ; Zhao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 78%
“…It was previously reported that the concentrations of chemical ions in the surface and groundwater of the study area were higher than those of atmospheric precipitation, while total phosphorus, total nitrogen, chlorophyll-a, and transparency values of the surface water pointed to eutrophication (Cui et al, 2021;Gao et al, 2022; Zhao et al, 2022). The trophic state index and bacterial eutrophic index values showed that the two lakes were slightly eutrophic (Gao et al, 2022;Zhao et al, 2022). These previously reported results indicate that the physicochemical properties of these two lakes affect the structure and function of the gut microbiota and ARGs in A. erythropus.…”
Section: Figurementioning
confidence: 82%
“…Fox et al [26] reported that an increase in aquatic vegetation attracts a large number of waterbirds. Therefore, the increase in the waterbird abundance after purse seine removal in Caizi Lake may be attributed to the substantial recovery of aquatic vegetation [46]. The artificial acceleration of the restoration of aquatic vegetation in Caizi Lake is conducive to the increase in the waterbird abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Caizi Lake has a long history of aquaculture. Net pens were constructed in the lake in the 1990s, covering more than 90% of its area [46]. Intensive aquaculture has destroyed aquatic vegetation, particularly submerged vegetation, throughout the lake.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation